Waste less time on Facebook — follow Brilliant.
×

Please help with math proof

HERE del(theta)/del(x) means partial derivative of theta with respect to x.Please Help with detailed solution...Thanks in advance...

Note by Raja Metronetizen
4 years, 1 month ago

No vote yet
1 vote

  Easy Math Editor

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 \( 2 \times 3 \)
2^{34} \( 2^{34} \)
a_{i-1} \( a_{i-1} \)
\frac{2}{3} \( \frac{2}{3} \)
\sqrt{2} \( \sqrt{2} \)
\sum_{i=1}^3 \( \sum_{i=1}^3 \)
\sin \theta \( \sin \theta \)
\boxed{123} \( \boxed{123} \)

Comments

Sort by:

Top Newest

Disregard my previous comment, this can be proved. We will begin with (ii), (though it doesn't really matter) because we will use the result of (ii) to prove (i).

\((x)^2 + (y)^2 = r^2\) \(\Rightarrow\) \(\frac{\partial} {\partial x}\)\(((x)^2 + (y)^2)\) = \((2r)(\frac{\partial r} {\partial x})\)

\(\Rightarrow\) \(2x = (2r)(\frac{\partial r} {\partial x})\)

\(\Rightarrow\) \(\frac{x} {r} = \frac {\partial r} {\partial x}\)

Note that \(cos(\theta)=\frac{x} {r}\),

Hence \(cos(\theta)=\frac {\partial r} {\partial x}\)

\(x=rcos(\theta)\) \(\Rightarrow\) \(\frac {\partial x} {\partial r} = \frac {\partial (rcos(\theta))} {\partial r}\)

\(\Rightarrow\) \(\frac{\partial x} {\partial r} = \frac {\partial r} {\partial x} = cos(\theta) \)

This proves (ii). Now for (i):

\(x=rcos(\theta)\) \(\Rightarrow\) \(\frac {\partial x} {\partial \theta} = \frac {\partial} {\partial \theta} (rcos(\theta))\) = \(-rsin(\theta)\)

\(\Rightarrow\) \((\frac {1} {r})\frac{\partial x} {\partial \theta}= -sin(\theta)\)

\(x=rcos(\theta)\) \(\Rightarrow\) \(\frac{\partial x} {\partial x}= \frac{\partial} {\partial x} (rcos(\theta)\)

\(\Rightarrow\) \(1= cos(\theta)\frac{\partial r} {\partial x} -rsin(\theta) \frac {\partial \theta} {\partial x}\)

In (ii) we showed that: \(\frac{\partial r} {\partial x} = cos(\theta)\), hence:

\(1=cos^2(\theta) - rsin(\theta)\frac {\partial \theta} {\partial x}\)

\(\Rightarrow\) \(\frac{1-cos^2(\theta)} {-rsin(\theta)}=\frac{\partial \theta} {\partial x}\)

\(\Rightarrow\) \(\frac {-sin(\theta)} {r} = \frac {\partial \theta} {\partial x}\)

\(\Rightarrow\) \(r\frac{\partial \theta} {\partial x} = -sin(\theta) = \frac {1} {r} \frac {\partial x} {\partial \theta}\)

This proves (i). Q.E.D.

Ethan Robinett - 3 years, 3 months ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...